The Relationship Between the Spine Curvature Disorders and the Resting Habits of University Students - Zahra Ghorbanpoor; Zahra Mosallanezhad; Javad Minaee Javid; Aileen Talimkhani; Nazila Akbar Fahimi (Physical Treatments, 2017)
Purpose: Considering the role of spine in protecting the body alignment and various body activities, this study aims to examine the relationship between the spine curvature disorders and resting habits among the students of the University of Social Welfare and Rehabilitation Sciences. Methods: In this correlational study, a total of 108 students of Tehran University of Social Welfare and Rehabilitation Sciences, aged 18 to 29 years, were selected through simple random sampling method. Their curvatures of their spines were measured by scoliometer and a flexible ruler, and their resting habits were assessed through the Resting Habits questionnaire. The obtained data were analyzed by performing Kolmogorov-Smirnov, linear regression, Pearson, Spearman, Mann-Whitney, and Independent t statistical tests using SPSS.V22. Results: There was no significant relationship between the resting habits of the study participants with their degrees of lordosis (P=0.858, r=0.574) and degree of scoliosis (P=0.603, r=0.857). However, there was a significant relationship between lordosis and gender (P<0.001) and age (P<0.022, r=0.22) in a way that the spine curvature disorders were more prevalent in girls and older students than boys and younger ones. Conclusion: In this study, the resting habits were not identified as risk factor for abnormal spine curvatures in the younger ages. However, bad resting habits at older ages and in females can be risk factors for lordosis.